The Quest for Polysulfides in Lithium–Sulfur Battery Electrolytes: An Operando Confocal Raman Spectroscopy Study. Issue 13 (1st September 2015) - Hannauer, Julien; Scheers, Johan; Fullenwarth, Julien; Fraisse, Bernard; Stievano, Lorenzo; Johansson, Patrik
Abstract The front cover artwork is provided by the groups of Prof. Lorenzo Stievano, (Université de Montpellier, FRANCE) and Prof. Patrik Johansson (Chalmers University of Technology, SWEDEN). The image represents the in situ spectro‐electrochemical cell used for the study of a lithium–sulfur battery for automotive applications by confocal Raman spectroscopy. This study allowed the identification of the polysulfides formed in the electrolyte. Read the full text of the article at 10.1002/cphc.201500448